1992
DOI: 10.5254/1.3538650
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Functional Polymers in Ground Rubber Tire-Polyethylene Composite

Abstract: The impact energies of different polyethylene-ground rubber tire (GRT) composites were investigated. All the thermoplastic composites were prepared on a Haake Buchler batch mixer and injection molded test specimens were tested on Rheometrics drop weight instrumented impact tester. Addition of small amounts of functional polymers increases the impact energy of the polyethylene-GRT composite as much as 60%. The percent improvement in the impact energy for linear low density polyethylene (LLDPE) and the composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 0 publications
0
39
0
1
Order By: Relevance
“…Baker and coworkers [11][12][13] reported that the use of several compatibilizers of ground rubber tires to improve the adhesion between ground rubber tires and thermoplastic matrices. One drawback of such blends is a comparatively weaker matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Baker and coworkers [11][12][13] reported that the use of several compatibilizers of ground rubber tires to improve the adhesion between ground rubber tires and thermoplastic matrices. One drawback of such blends is a comparatively weaker matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, GTR can be used as either treated [11][12][13][14] or untreated. 15 Treated GTR can provide promoted interfacial adhesion, which may lead to better mechanical performance, but its large-scale utilization is normally hindered by the high cost.…”
Section: Introductionmentioning
confidence: 99%
“…1 Effective recycling technology persists be a matter of interest in rubber waste recycling, pyrolysis and landfills result in ecological complications. [2][3][4][5] The trapped air by the void areas, in case of tubular rubber products like hoses, pipes, and tubes cause the land filled products to rise to surface in no time. 6 Moreover, due to the confined purview of space and available landfill sites and due to the corresponding cost explosion 7 this process of waste rubber disposal is no longer feasible.…”
Section: Introductionmentioning
confidence: 99%